Les membranophones des Luba-Shankadi - Laurenty, J. S. (International Library of African Music, 1972)
Les membranophones des Luba-Shankadi
Keywords: Ethnomusicology; Music; Drum; Luba (African people); Musical instruments; Africa; Central Africa; Drum music; African Music; Drum (Instrument)